Ultrasound anatomy of the transversus abdominis plane region in pregnant women before and after cesarean delivery. Issue 1 (December 2016) - Kiefer, Nicholas; Krahe, Stefanie; Gembruch, Ulrich; Weber, Stefan
Abstract Background After cesarean delivery, analgesia is often incomplete and a multimodal approach to analgesia is necessary. Transverse abdominal plane (TAP) block has been advocated in this setting, yet no systematic description of the ultrasound anatomy in pregnant women exists in the literature. Therefore, we aimed to describe the sonographical features of relevant structures in pregnant women before and after elective cesarean. Methods Sixty women at, or close to term scheduled for elective cesarean delivery underwent a standardized ultrasound examination before and after delivery. We assessed the visibility of the muscular layers and measured the distance from the skin to the layers of the abdominal wall muscles in the region for TAP block before and after cesarean section on both side. Results The three muscular layers of the lateral abdominal wall (external oblique, internal oblique and transversus abdominis muscle) were visible in all examinations. Before cesarean section the median TAP distance was shorter: 2.9 cm (interquartile range 2.6–3.6) compared to 3.9 cm (3.1–4.5) after cesarean section (left side, p  < 0.001). The external and internal oblique muscles were located closer to the skin surface before cesarean section. An increased body mass is associated with increased the TAP distance before and after birth (p  < 0.001). Conclusion Relevant anatomical landmarks for a TAP block are sonographically well visible after cesarean delivery. Postoperatively, depth of the TAP as compared to before birth is increased significantly. Scanning the abdominal wall before CD will underestimate the target depth of the TAP after delivery. The obstetric anesthetist needs to be aware of these changes when planning a TAP block in the context of cesarean delivery.